2022
DOI: 10.1029/2022ja030844
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Nighttime Ionospheric NmF2 Enhancement at Middle‐to‐High Latitudes in the Northern Hemisphere

Abstract: The electron density in the ionosphere usually continuously decreases during nighttime due to the vanishing of sunlit ionization. However, it sometimes increases unexpectedly, which has been called nighttime ionospheric enhancement. Previous researches studied this type of phenomenon mainly in the low‐to‐middle latitude regions. Here, we investigate the nighttime ionospheric NmF2 enhancement at middle‐to‐high latitudes in the northern hemisphere (NH) during solar cycles 23–24 by analyzing the ionosonde observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Zhao et al. (2022) find that the injection of plasma from the plasmasphere to the nightside ionosphere may leads to the enhancement of plasma density using statistical analysis and simulation (E‐CHAIM model). In their study, nightside electron density enhancement has a clear polar boundary which coincides with the polar boundary of the plasmasphere, and related to the position of mid‐latitude ionospheric trough.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al. (2022) find that the injection of plasma from the plasmasphere to the nightside ionosphere may leads to the enhancement of plasma density using statistical analysis and simulation (E‐CHAIM model). In their study, nightside electron density enhancement has a clear polar boundary which coincides with the polar boundary of the plasmasphere, and related to the position of mid‐latitude ionospheric trough.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with the Ionospheric Observational Network for Irregularity and Scintillation in East and Southeast Asia (IONISE) (Li et al, 2019;Sun et al, 2020), various ionospheric phenomena as well as their possible mechanisms can be investigated in detail in the East Asia region. Among these phenomena, nighttime enhancement is a topic worthy of attention and has been extensively studied recently as regard to its temporal, spatial, seasonal, solar and geomagnetic activity dependences (e.g., Chen C. et al, 2012;Chen et al, 2015aChen et al, , 2015bLi et al, 2020;Liu et al, 2013Liu et al, , 2020Liu et al, , 2023Sahu et al, 2020;Wang et al, 2022;Zhao et al, 2022;Zhong et al, 2019). The mechanism of the nighttime enhancement is predominantly believed to be latitude dependent, indicating that equatorward neutral wind and field-aligned plasma transport dominate at middle latitude while westward electric field should be responsible for the low latitude feature observed like in Sanya (Le et al, 2014;Li et al, 2020;Lin et al, 2010;Liu et al, 2013Liu et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Jakowski et al (2015) pointed out that the NWA is usually found in longitude sectors where the difference between the geomagnetic equator and the geographic equator is maximized. Utilizing the empirical model E-CHAIM, Zhao et al (2022) studied the ionosphere nighttime enhancement of the peak electron density of the ionospheric F2-layer (NmF 2 ) at mid-and high-latitude in the Northern Hemisphere and found that the longitudinal differences of the enhancement as the local minimum at 20°W and the local maximum at 75°E as well as 120°W were found. (The definition of the abbreviations used in this paper at parts to ease readability, is summarized in Table 1.)…”
mentioning
confidence: 99%